Situation Report: Hungary, 18 November 1969 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Popular Demand Clashes with Regime's Cultural Policy Promotion in State Church Office New Director at the Hungarian Papal Institute in Rome Foreign Trade in 1969 General Consumer and Marketing Co-operatives Create a Share Company New Hotels to Attract Western Tourists Price Increases, the Reform, and the Public "Refloating" an Insolvent Wholesale Enterprise The Pork Shortage - An Important Political Question Attempt to Improve Co-operation between Canned Food Industry and the Farmers' Co-Operatives